2017
DOI: 10.1038/cddis.2016.493
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus X protein promotes the stem-like properties of OV6+ cancer cells in hepatocellular carcinoma

Abstract: Hepatitis B virus X protein (HBx) and cancer stem-like cells (CSCs) have both been implicated in the occurrence and development of HBV-related hepatocellular carcinoma (HCC). However, whether HBx contributes to the stem-like properties of OV6+ CSCs in HCC remains elusive. In this study, we showed that the concomitant expression of HBx and OV6 was closely associated with the clinical outcomes and prognosis of patients with HBV-related HCC. HBx was required for the stem-like properties of OV6+ liver CSCs, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 47 publications
1
40
0
Order By: Relevance
“…By IHC, the positive staining for OV6 in normal prostate basal cells suggests that OV6 is an epithelial marker ( Fig. 1A), which is consistent with the results of our previous studies (24)(25)(26)(27). Samples from locally advanced prostate cancer (LAPC), CRPC, and neuroendocrine prostate cancer (NEPC) exhibited higher OV6 expression than localized prostate cancers (Fig.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…By IHC, the positive staining for OV6 in normal prostate basal cells suggests that OV6 is an epithelial marker ( Fig. 1A), which is consistent with the results of our previous studies (24)(25)(26)(27). Samples from locally advanced prostate cancer (LAPC), CRPC, and neuroendocrine prostate cancer (NEPC) exhibited higher OV6 expression than localized prostate cancers (Fig.…”
Section: Resultssupporting
confidence: 90%
“…In this study, we demonstrated that a subpopulation in prostate cancer harboring CSC characteristics could be identified by the epithelial marker OV6, which serves as a CSC marker in epithelium-derived malignant tumors and was associated with patient prognosis in our previous studies (24)(25)(26)(27). We demonstrated that an intracellular pathway, autophagy-related gene 7 (ATG7)/ b-catenin/OCT4, sustained the self-renewal of OV6 þ cells and facilitated the progression and ADT resistance of prostate cancer.…”
Section: Introductionmentioning
confidence: 62%
“…On the other hand, HBx exhibited functions through alteration of cellular localization of proteins involved in cell growth. For example, HBx bound to murine double minute 2 (MDM2) and promoted its translocation into the nucleus, resulting in enhanced transcriptional activity of MDM2 . Our data demonstrated that HBx enhanced 14‐3‐3β–mediated cytoplasmic retaining of SRSF3.…”
Section: Discussionmentioning
confidence: 99%
“…The link between HBx-expressing and CSCs in HBV-related HCC has gradually become a research hotspots. It has been reported that HBx promoted a CD44 + CD133 + CSCs subset in malignant transformed L-02 cells and Huh7 cells, and HBx regulated tumorigenicity, self-renewal, and drug resistance in HCC cells [4,35,36]. In the present study, we selected two different HCC cells with distinct proportion of ABCG2 + subset, which Huh7 cells had a low ABCG2 + subset ratio and MHCC-97H had a high ABCG2+ subset ratio.…”
Section: Discussionmentioning
confidence: 95%